Managers' investment decisions: Incentives and economic consequences arising from leases - Tim V. Eaton; Craig Nichols; James Michael Wahlen; Matthew Wieland (Journal of Risk and Financial Management, 2021)
What incentives do managers face that might give rise to inefficient investments in leases? If managers make inefficient investments in leases, what economic consequences arise for those managers and their firms? We develop a model of expected investments in leased assets and use the residuals from the model as proxies for inefficient investments. We find that, in contrast to investments in capital expenditures, leasing appears to be a mechanism through which managers can seemingly over-invest, even among firms with high quality financial reporting and negative free cash flows. Examining economic consequences, we predict and find that unexpected investments in leased assets trigger increasing future sales growth but declining future earnings growth for as long as three years ahead. We also find a negative relation with contemporaneous stock returns, suggesting investors view unexpected investments in leases as value destructive. Finally, despite negative returns consequences, we find that unexpected investments in leases are associated with higher CEO compensation driven primarily by future sales growth. Our study suggests that compensation contracts that reward growth may give managers' incentives to drive sales growth with larger-than-expected investments in leased assets, which lead to slower future earnings growth and negative share price consequences for investors. Our results should inform managers and board members, investors, and researchers interested in investment efficiency, corporate governance, and leases.
Keywords: 330; corporate governance; compensation; earnings growth; investment; leases; sales growth; stock returns